Tai Chi Improves Cognition and Plasma BDNF in Older Adults With Mild Cognitive Impairment: A Randomized Controlled Trial - Somporn Sungkarat (2018)
© 2018, © The Author(s) 2018. Background. Effects of Tai Chi (TC) on specific cognitive function and mechanisms by which TC may improve cognition in older adults with amnestic mild cognitive impairment (a-MCI) remain unknown. Objective. To examine the effects of TC on cognitive functions and plasma biomarkers (brain-derived neurotrophic factor [BDNF], tumor necrosis factor-α [TNF-α], and interleukin-10 [IL-10]) in a-MCI. Methods. A total of 66 older adults with a-MCI (mean age = 67.9 years) were randomized to either a TC (n = 33) or a control group (n = 33). Participants in the TC group learned TC with a certified instructor and then practiced at home for 50 min/session, 3 times/wk for 6 months. The control group received educational material that covered information related to cognition. The primary outcome was cognitive performance, including Logical Memory (LM) delayed recall, Block Design, Digit Span, and Trail Making Test B minus A (TMT B-A). The secondary outcomes were plasma biomarkers, including BDNF, TNF-α, and IL-10. Results. At the end of the trial, performance on the LM and TMT B-A was significantly better in the TC group compared with the control group after adjusting for age, gender, and education (P <.05). Plasma BDNF level was significantly increased for the TC group, whereas the other outcome measures were similar between the 2 groups after adjusting for age and gender (P <.05). Conclusions. TC training significantly improved memory and the mental switching component of executive function in older adults with a-MCI, possibly via an upregulation of BDNF.